Primary Pleural Lymphoma: Case Report - Flores-Uzcanga, Maura Alicia; Tovar-Becerra, Andrea Itzel; Narváez-Anzures, Edgar Omar; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
We report a case of a 70-year-old female with a history of prolonged exposure to biomass during childhood, non-smoker and no history of exposure to people with tuberculosis who presented with progressive dyspnea. Chest CT showed circumferential and nodular suitable pleural thickening with involvement of the mediastinal pleura and ipsilateral pleural effusion. An ultrasound-guided pleural biopsy was performed with a Trucut needle. The Histopathology result of the pleural biopsy determined an infiltration due to non-Hodkin lymphoma of lineage B. Immunohistochemistry CD20 positive, CD3 Positive. This case is thought to be a very rare case of primary malignant lymphoma arising in the pleura without a history of chronic pleural inflammation or immunocompromise.